(untitled) (Dialogos, 2017)
O texto pretende debater o problema da investigação do historiador a partir dos arquivos particulares, trabalhar as dificuldades da reconstrução de trajetos políticos dos exilados nos países de acolhimento e analisar os caminhos a percorrer pelo historiador na sua pesquisa a respeito das redes de contacto dos exilados. Tomaremos por base a pesquisa realizada sobre os exilados portugueses republicanos em Espanha e no Brasil Abstract Files and reconstruction of life histories: the dimension transnational and transcultural the exiles This paper intends to debate the historian´s problems regarding private archives and exiles. It deals with the difficulties of reconstructing the political roots of the exiles in their host countries and analyses the ways the historian must work in order to reconstruct the networks among the exiles. The article is based on research about the Portuguese Republican exiles in Spain and Brazil.